Procedural Reform to the System of Expert Evidence in Medical Negligence Cases in Malaysia - Lee, Joseph (Journal of Malaysian and Comparative Law, 2019)
The system of expert evidence in medical negligence cases in Malaysia is adversarial. Under the rules of the court, litigants may engage their own medical experts to advance their case although limited authority is conferred upon a High Court judge to appoint an independent expert. Although medical experts owe an obligation to the court to be impartial in their testimony, judicial commentary from Malaysia, United Kingdom and Australia shows that this common law duty has failed to curb the problem of biased expert testimony. Whilst the United Kingdom and most state jurisdictions in Australia have implemented procedural reform to move away from the system of litigant-appointed experts in, among others, medical negligence proceedings, there is no indication that Malaysia is heading towards any form of procedural reform. This article analyses the problems facing the use of experts in medical negligence litigation in Malaysia and argues for procedural reforms by drawing on the developments in the United Kingdom and Australia.